Securing maize reproductive success under drought stress by harnessing CO2 fertilization for greater productivity - Li, Yangyang; Zhang, Pengpeng; Sheng, Wenjing; Zhang, Zixiang; Rose, Ray J.; Song, Youhong (Frontiers in Plant Science, 2023)
Securing maize grain yield is crucial to meet food and energy needs for the future growing population, especially under frequent drought events and elevated CO 2 (eCO 2 ) due to climate change. To maximize the kernel setting rate under drought stress is a key strategy in battling against the negative impacts. Firstly, we summarize the major limitations to leaf source and kernel sink in maize under drought stress, and identified that loss in grain yield is mainly attributed to reduced kernel set. Reproductive drought tolerance can be realized by collective contribution with a greater assimilate import into ear, more available sugars for ovary and silk use, and higher capacity to remobilize assimilate reserve. As such, utilization of CO 2 fertilization by improved photosynthesis and greater reserve remobilization is a key strategy for coping with drought stress under climate change condition. We propose that optimizing planting methods and mining natural genetic variation still need to be done continuously, meanwhile, by virtue of advanced genetic engineering and plant phenomics tools, the breeding program of higher photosynthetic efficiency maize varieties adapted to eCO 2 can be accelerated. Consequently, stabilizing maize production under drought stress can be achieved by securing reproductive success by harnessing CO 2 fertilization.